Regulating the maritime navigation of the future: UNCLOS and the work on the regulation of maritime autonomous surface ships (MASS) at the International Maritime Organisation - Pacheco de Freitas, José Augusto (2023)
The regulation of maritime autonomous surface ships (MASS) will need to redefine the traditional legal and conceptual categories of the law of the sea, whose rules were adopted over the basis that ships were manned by a master and crew on board.An evolutionary interpretation of UNCLOS allows to justifiy that the IMO endeavours to regulate the operation of MASS. Within this framework, the IMO has completed an exploratory study, in which it adopted a preliminary definition of autonomous ships and identified three high-priority themes: the meaning of the terms master, crew, or responsible person; the consideration of the remote-control station or centre; and the possibility to designate remote operators as seafarers. Subsequently, the IMO established in 2022 a workplan to adopt a goal-based non-mandatory MASS Code in 2024 and a mandatory Code in 2025.Following the exploratory study and the workplan, the negotiations for the regulation of MASS at the IMO began in 2022. This ongoing work is considering how to adapt the existing regulation to allow States to operate MASS in compliance with the obligations and rights provided in UNCLOS and the IMO instruments, ensuring maritime safety.